Klasika: Program Analisis Item dan Tes dengan Pendekatan Klasik - Hayat, Bahrul (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2021)
This article introduces the Klasika software developed to run item and test analysis using the Classical Test Theory approach. Classical Test Theory is one of the specialized competencies and skills that undergraduate students of psychology must possess. Classical Test Theory becomes a mandatory course for all schools or departments of psychology in Indonesia. This article also provides a theoretical foundation of Classical Test Theory's essential concepts and statistical methods, specifically related to items and test statistics. The item analysis and test reliability procedures using Klasika, starting from the data preparation untill data interpretation, are explained with an empirical illustration. Finally, the analysis results using Klasika are compared with the results from Quest software to test the accuracy of the estimation results.